Developing Lightweight Clay Brick Units Using Waste Materials - Sabah Abed, Musaab; Fahad Resan, Sa'ad; Kamil Zemam, Sajid (International Journal of Engineering and Technology, 2018)
The study aims to develop specific lightweight brick units using locally available clay of traditional burned brick units publically used in the south of Iraq using solid wastes. Throughout the study, chemically inaction and difficult to recycling wastes was considered, they were classified into Poly Vinyl Chloride (PVC) and hardwood solid waste which is used to upgrade lightweight characteristic and maintenance required bricks' characteristics and to be introduced as a smart technical way to recycling solid waste. Solid waste is introduced as additive materials and firing fuel enhanced coefficient in the concept of its energy recovery useful in the production process.Â  An experimental program was considered including five main series of samples, tested and analyzed in the scope of clay bricks units and in the scope of lightweight constructional related to aerated wall construction units. The verified compressive strengths and other properties of tested specimens were found to confirm bricks class C except for specimens of hardwood of 10% although it assigns less dry density (1.18 g/cm3). In general, as light weight bricks, the characteristics of developed units was found to be within the permitted limits of ASTM C 1389.Â